Proceedings of the 20th International ACM SIGACCESS Conference on Computers and Accessibility 2018
DOI: 10.1145/3234695.3241481
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing - An Aphasia Perspective

Abstract: This paper reports the experience of participating in usability testing from the perspective of a person with aphasia. We briefly report adaptations to classic usability testing to enable the participation of people with aphasia. These included the use of short, direct tasks and physical artefacts such as picture cards. Authors of the paper include Ian, a user with aphasia who participated in adapted usability testing and Abi, a speech and language therapist researcher who facilitated sessions. Ian reports tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Research indicates, however, that the language demands implicit in many aspects of technologyuse present barriers for people with aphasia [8,20,32,40]. The testing of social media tools with people with aphasia [39], for example, has shown that they can present a number of barriers [21]. This means that many creativity support tools, such as those described previously, are not available.…”
Section: Aphasia and Content Creationmentioning
confidence: 99%
“…Research indicates, however, that the language demands implicit in many aspects of technologyuse present barriers for people with aphasia [8,20,32,40]. The testing of social media tools with people with aphasia [39], for example, has shown that they can present a number of barriers [21]. This means that many creativity support tools, such as those described previously, are not available.…”
Section: Aphasia and Content Creationmentioning
confidence: 99%
“…Many digital technologies are challenging for people with aphasia [27,37] due to their language demands. Even commonplace tools such as social media platforms can present signiicant barriers [19,36]. The Snapchat social media platform has been explored as a tool to support expression and engagement between users with aphasia [3].…”
Section: Background 21 Aphasia and Tools For Creativity And Self-expr...mentioning
confidence: 99%
“…4.1.2 Voices of People with Aphasia. Descriptions of life with mild to moderate aphasia from YouTube videos [44,45,47] created by people with aphasia and a paper [36] co-authored by a person with aphasia were used to develop empathy with the intended users and to focus the goals and requirements of Comic Spin. Key takeaways included:…”
Section: Empathize and Definementioning
confidence: 99%
See 1 more Smart Citation
“…The participation of people with aphasia in the research and design of new technologies has been the focus of some attention. (Wilson et al, 2015;Roper et al, 2018;Kearns et al, 2020). This paper describes a somewhat unusual example of this phenomenon, in which a stroke survivor and his wife worked together with a speech language pathologist (who they met in rehab) to create a mobile app to help people recovering from brain injuries.…”
Section: Introductionmentioning
confidence: 99%